Modeling of the optimal structure of meat processing enterprises - Марич, Максим; Kovalchuk, Natalia; Rusul, Liubov; Viknianska, Anastasiia (My University, 2019)
In today’s economic conditions, problems of functioning of domestic enterprises are not limited by lack of sources of financing of assets, but also often associated with inefficient investment in specific components of property, which adversely affects the level of economic efficiency of Ukrainian enterprises and the development of the economy as a whole. An important factor in making sound, rational and sound decisions about asset management is to improve existing or develop fundamentally new methods and models for optimizing the structure of assets of Ukrainian enterprises using criteria that are most relevant to current economic requirements, environmental challenges and internal objectives. In view of the above, the article demonstrates a clear dependence of the structure of the assets of the enterprise and the key indicators that characterize the effectiveness of its management. The optimal structure of assets for the studied enterprises and possible ways of their achievement are offered taking into account the defined criteria. A comparative assessment of the assets structure of the surveyed enterprises before and after optimization was carried out and on this basis the latter was confirmed by comparing the key parameters of the enterprise performance — profit and market value. A clear sequence of stages of the asset structure optimization model is proposed and described, along with methodological aspects of determining the effective structure of assets, the feasibility of its practical application at Ukrainian enterprises is proved through the achievement of the key goal of the enterprise activity — maximization of market value and profit.
Keywords: assets; asset structure; optimization; factor analysis; econometric model; profit growth; increase in market value